Perception and Willingness Regarding Organ Transplantation/donation among Medical Students of Maharajgunj Medical Campus: A Cross-sectional Study - Bhattarai, Amit Sharma; Adhikari, Bidur; Joshi, Deepak Raj; Yadav, Alisha; Joshi, Pankaj; Parajuli, Bashu Dev; Koirala, Megha; Karki, Kushal Jung; Subedi, Krishna Prasad; Shrestha, Gentle Sunder; Shrestha, Anil; Singh, Shreejana (Journal of Nepal Health Research Council, 2024)
Background: Organ transplant is the procedure of replacing a failing or damaged organ with a functioning one. Positive attitude and awareness about donation are a must for donor organs to be available. This study explored the level of knowledge, perception and willingness regarding organ donation among medical students in Nepal. Methods: A descriptive cross-sectional study was conducted with 180 medical students using a self-administered questionnaire. Descriptive statistics were used, and Pearson correlation was applied to examine the relationship between knowledge and perception of organ transplantation. Independent samples t-test and ANOVA was used to compare scores among year of study and gender. Results: Results indicated that 86.1% of participants were aware of the need for organ donation, and 83.3% knew that both living and deceased individuals could be donors. While 93.9% believed in the need for effective laws, 72.8% perceived risks for donors. However, only 74.4% were willing to donate their organs, though 91.7% expressed willingness to promote organ donation among friends and family. Participants showed a positive perception towards organ donation. Conclusions: Despite a high level of awareness and knowledge regarding organ donation, participants exhibited a lower level of willingness to donate organs. Perceived risks for donors and a lack of robust laws and regulations presented significant barriers. Nevertheless, an inclination to promote organ donation was observed. This underlines the need for enhanced education and policy reform to increase organ donation rates. Keywords: Awareness; knowledge; organ donation; organ transplantation; perception.